Chemical and Plant-Based Insect Repellents: Efficacy, Safety, and Toxicity - Diaz, James H. (Wilderness & environmental medicine, 2016)
Most emerging infectious diseases today are arthropod-borne and cannot be prevented by vaccinations. Because insect repellents offer important topical barriers of personal protection from arthropod-borne infectious diseases, the main objectives of this article were to describe the growing threats to public health from emerging arthropod-borne infectious diseases, to define the differences between insect repellents and insecticides, and to compare the efficacies and toxicities of chemical and plant-derived insect repellents. Internet search engines were queried with key words to identify scientific articles on the efficacy, safety, and toxicity of chemical and plant-derived topical insect repellants and insecticides to meet these objectives. Data sources reviewed included case reports; case series; observational, longitudinal, and surveillance studies; and entomological and toxicological studies. Descriptive analysis of the data sources identified the most effective application of insect repellents as a combination of topical chemical repellents, either N-diethyl-3-methylbenzamide (formerly N, N-diethyl-m-toluamide, or DEET) or picaridin, and permethrin-impregnated or other pyrethroid-impregnated clothing over topically treated skin. The insecticide-treated clothing would provide contact-level insecticidal effects and provide better, longer lasting protection against malaria-transmitting mosquitoes and ticks than topical DEET or picaridin alone. In special cases, where environmental exposures to disease-transmitting ticks, biting midges, sandflies, or blackflies are anticipated, topical insect repellents containing IR3535, picaridin, or oil of lemon eucalyptus (p-menthane-3, 8-diol or PMD) would offer better topical protection than topical DEET alone.